Time perception and lived experience in personality disorders: differences across types, dimensions and severity - Sterna, Anna; Sakakibara, Eisuke; Moskalewicz, Marcin (PeerJ, 2025)
Background Altered temporal experience lies at the core of various psychiatric conditions, including borderline personality disorder (BPD). Mainstream research in psychopathology tends to explore BPD with scrutiny while neglecting other personality disorders (PD). At the same time, the dimensional approach to PD proposes looking through the disorders’ subtypes and tracing lived experience-based commonalities. This study is the first to explore the temporality of PD by investigating the relationship between symptom severity and lived time and combining objectified measures of time perception with phenomenological interpretation. Methods A total of 63 participants of various educational backgrounds, with personality disorders (36.5% male), following ICD-10 coding diagnosed with paranoid (3.2%), borderline (41.3%), narcissistic (33.3%), avoidant (4.8%), dependent (1.6%) and unspecified (15.9%) personality disorder. Levels of personality functioning and intensity of maladaptive trait domains were controlled with Level of Personality Functioning—Brief Scale 2.0 and Personality Inventory for ICD-11, respectively, resulting in the overall sample classification as comprising nine subclinical, 13 mild, 20 moderate, 16 severe, and five extremely severe conditions. Polish Short Version of the Zimbardo Time Perspective Inventory (PS-ZTPI) and Cottle’s Circles Test (CT) were used to assess the temporal experience. Results In comparison to healthy individuals, those with PD are more oriented toward past negative (4.01 vs. 2.98) and less toward past positive (2.31 vs. 3.71) and future (3.04 vs. 3.47), as measured with PS-ZTPI; their pre-reflective temporal experience, as measured with CT, is dominated either by the past or the future, while the present remains marginalized. BPD distinctiveness among other PD lies in higher orientation toward hedonistic present and lower orientation toward the future. While the general temporal profile of PD is independent of age and duration of hospitalization, it is related to the severity of the condition. The more severe the impairments in self-functioning, the higher the negative past perspective and pre-reflective past dominance, and the lower the positive and future perspective. The results of this study highlight temporality as an essential aspect of lived experience in PD, being possibly related to disturbed self-experience.
Keywords: Phenomenology; Psychopathology; Lived experience; Zimbardo time perspective inventory; Borderline personality disorder; Narcissistic personality disorder; Dimensional diagnosis; First person experience; Self disturbance; DSM-5